2018
DOI: 10.7567/jjap.57.062801
|View full text |Cite
|
Sign up to set email alerts
|

Two-step frequency conversion for connecting distant quantum memories by transmission through an optical fiber

Abstract: Long-distance quantum communication requires entanglement between distant quantum memories. For the purpose, photon transmission is necessary to connect the distant memories.Here, for the first time, we develop a two-step frequency conversion process (from a visible wavelength to a telecommunication wavelength and back) involving the use of independent two-frequency conversion media where target quantum memories are nitrogen-vacancy centers in diamonds (with an emission/absorption wavelength of 637.2 nm), and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The WC-TPC has two important parameters: noise floor level and signalto-noise ratio (SNR). The noise floor level is influenced by many factors, including the presence of a residual laser, which can induce other nonlinear processes such as SPDC and Raman scattering 36,37 , dark counts in the detector, and stray light (related results are presented in Supplementary Note 5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The WC-TPC has two important parameters: noise floor level and signalto-noise ratio (SNR). The noise floor level is influenced by many factors, including the presence of a residual laser, which can induce other nonlinear processes such as SPDC and Raman scattering 36,37 , dark counts in the detector, and stray light (related results are presented in Supplementary Note 5).…”
Section: Resultsmentioning
confidence: 99%
“…The noise floor level is influenced by many factors, including the presence of a residual laser, which can induce other nonlinear processes such as SPDC and Raman scattering [36] [37], dark counts in the detector, and stray light (related results are presented in the Supplementary note 5). Two-photon correlation was characterized by the normalized second-order signal-idler correlation coefficient g 𝑠,𝑖…”
Section: Wavelength-converted Two-photon Combmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed beam profile is sufficient for obtaining a highefficiency coupling to a wavelength conversion medium, such as a waveguide-type periodically poled lithium niobate (PPLN). In a previous work by several authors of the present study [19], the maximum wavelength conversion between 637.2 nm and a telecommunication wavelength was achieved with a pump power of about 500 mW where another laser with a slightly different wavelength (1071 nm) was used. However, we also demonstrated the same wavelength conversion process with the present laser and achieved a maximum conversion efficiency up to 35 % with a pump laser power of about 300 mW.…”
Section: Discussionmentioning
confidence: 65%
“…This is due to non-phase-matched broadband spontaneous parametric down conversion (SPDC) of the pump laser [14]. This noise contribution scales linearly with the pump power, as observed and verified in numerous experiments [11,12,14,17]. Yet, recent experiments have shown that the noise can be suppressed to acceptable levels by strong filtering around the target wavelength [5,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 93%